Becoming Muhammad Ali : a novel - Patterson, James, 1947-; Alexander, Kwame; Anyabwile, Dawud, 1965- (New York : Jimmy Patterson Books, Little, Brown and Company, 2020)
This novel in verse tells the story of Cassius Clay, the determined boy who would one day become Muhammad Ali, one of the greatest boxers of all time.
School Library Journal starred, October 2020
Booklist starred, October 2020
Horn Book Starred, November 2020
Pub Weekly, September 2020
Kirkus Starred, August 2020
Includes bibliographical references (pages 307-308).
Keywords: Ali, Muhammad, -- 1942-2016 -- Juvenile fiction; Boxers (Sports) -- Juvenile fiction; African Americans -- Juvenile fiction; Ali, Muhammad, -- 1942-2016 -- Fiction; African Americans -- Fiction; Biographical fiction; Novels in verse; Boxers (Sports)